INTEGRATED AIR STERILIZATION SYSTEM BASED ON PLASMA NANOBUBLE OZONE TECHNOLOGY WITH INTERNET OF THINGS - Shafina Rifdhayanti Zein; Waru Djuriatno; Adharul Muttaqin (Jurnal Mahasiswa TEUB, 2023)
Bacteria and viruses are rapidly spreading around the world with a significant mortality rate of 7.8 per cent. The spread and transmission of bacteria and viruses in closed environments is generally riskier than in open environments. To reduce this, technology was needed that technology that can overcome these problems through the innovation of an IoT-integrated air sterilizer to show air conditions in real time that can be accessed via a smartphone. This technology adopts 3 stages of filtration The latest filtration stages are HEPA Filter, UV-C, and ozone. ozone can destroy viruses and bacteria to cause damage to the DNA and RNA of the virus. DNA and RNA through the destruction of spike proteins and the lipid layer. One method to produce ozone uses the high voltage plasma method. Ozone administration with a concentration of 0.06 ppm-0.1 ppm can reduce viral andbacterial activity up to 3-log reduction. However, the use of ozone above 0.08 ppm can cause health problems in humans. In addition, it was found that O2 with a movement speed of 1.25 m/s with a voltage of 4.5-5 kV will produce ozone with a concentration of 0.061 ppm which is effective and safe for humans. In addition to the use of ozone, the use of UV-C light is able to break down RNA and DNA in the SARS-CoV-2 virus with a minimum energy of 5.92x1011 eV per second in a unit area of cm2. To produce this amount of photon energy, UV-C light with a wavelength of 209 nm can be obtained. Therefore, this scientific paper discusses the analysis of ozone generation with high voltage plasma and the analysis of photon energy emission in UV-C light that is effective in inactivating viruses and bacteria. Keywords: Bacteria, Viruses , High Voltage Plasma, Ozone, UV-C Light